Promoting Religious Moderation in Public Schools: An Analysis of Islamic Religious Education - Hak, M. Aji Asnal; Achdi, Muh. Wasitch (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
Indonesia faces challenges of diversity and rising exclusivity, which demand proactive strategies to foster social cohesion. In response to these dynamics and internal school incidents, strengthening religious moderation has become urgent for shaping inclusive student character. This study examines the implementation of religious moderation at SMA Negeri 1 Banguntapan, Yogyakarta, using a qualitative case study approach. Data were collected through interviews with Islamic Religious Education (PAI) teachers and the school’s quality assurance team. Analysis followed the Miles and Huberman interactive model, and data validity was ensured through triangulation of sources and techniques. The results indicate that the program is driven not only by government directives but also by an internal crisis (the 2022 hijab case) and the broader vision of preparing students for the post-truth era. Implementation occurs through three main strategies: (1) daily practices combining religious rituals and nationalism, (2) integration of moderation values into PAI as a hidden curriculum, and (3) fostering an inclusive school culture grounded in local wisdom. Evaluation is conducted through the National Assessment and internal supervision. The program has demonstrated a positive impact on students’ tolerance and critical thinking skills. This study recommends an adaptive model for integrating religious moderation in public schools. Abstrak: Indonesia menghadapi tantangan keberagaman dan menguatnya eksklusivitas yang menuntut strategi proaktif dalam merawat kebhinekaan. Merespons dinamika tersebut serta insiden internal sekolah, penguatan moderasi beragama menjadi urgensi untuk membentuk karakter siswa yang inklusif. Penelitian ini bertujuan untuk mengkaji penerapan moderasi beragama di SMA Negeri 1 Banguntapan, Yogyakarta. Penelitian ini bertujuan mengkaji penerapan moderasi beragama di SMA Negeri 1 Banguntapan menggunakan pendekatan kualitatif studi kasus. Data dikumpulkan melalui wawancara dengan guru PAI dan tim penjamin mutu sekolah. Analisis data dilakukan menggunakan model interaktif Miles dan Huberman, sedangkan validitas data diuji melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa program ini tidak hanya didorong oleh instruksi pemerintah, tetapi juga respons terhadap krisis internal (kasus jilbab 2022) dan visi menghadapi era post-truth. Implementasi dijalankan melalui tiga strategi utama: (1) pembiasaan harian yang menyatukan ritual agama dan nasionalisme; (2) integrasi nilai moderasi dalam PAI sebagai hidden curriculum; dan (3) budaya sekolah inklusif berbasis kearifan lokal. Evaluasi dilakukan melalui Asesmen Nasional dan pengawasan internal. Program ini terbukti berdampak positif pada peningkatan toleransi dan kemampuan berpikir kritis siswa. Studi ini merekomendasikan model integrasi moderasi beragama adaptif di sekolah umum.